Benefits of Coriandrum sativum L. seed extract in maintaining immunocompetent cell homeostasis - Sri Rahayu,; Rifa’i, Muhaimin; Dahliatul Qosimah,; Sri Widyarti,; Noviana Dwi Lestari,; Jatmiko, Yoga Dwi; Putra, Wira Eka; Tsuboi, Hideo (Penerbit Universiti Kebangsaan Malaysia, 2022)
Diabetes mellitus (DM) is a metabolic disease followed by an increase in blood glucose and impaired metabolism of proteins, lipids and carbohydrates. In general, these conditions are caused by impaired insulin secretion and/or defects of insulin receptors. As yet, there is no effective drug capable of treating DM. Manifestations of DM worsen when accompanied by severe inflammation. Therefore, the avoiding strategy and management of inflammation in DM are the primary courses of action in preventing further damage. In this study, we had evidence that Coriandrum sativum L. extract (CSE) could be used as an alternative to relieve symptoms in DM mice model. Previously, CSE has been shown to be able to inhibit the synthesis of the pro-inflammatory molecule interleukin (IL)-6 by both B220 and CD11b cells. Here, we showed that CSE prevents over-activation of CD4 and CD8 T lymphocytes. The predominance of T cells expressing CD62L on both CD4 and CD8 T cells after administration of CSE indicated that there were obstacles to activation. CSE also suppressed excessive CD25 expression, causing CD25 expression in CD4 T cells to return to normal levels. Thus, this study showed the therapeutic activity of CSE in DM mice model by suppressing the pro-inflammatory cytokines, modulate the activation of naïve T cells, and maintain the population of CD4+ CD25+ cells.